2016
DOI: 10.1080/02640414.2016.1221521
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for assessment of muscle force, velocity, and power producing capacities from functional movement tasks

Abstract: A range of force (F) and velocity (V) data obtained from functional movement tasks (e.g., running, jumping, throwing, lifting, cycling) performed under variety of external loads have typically revealed strong and approximately linear F-V relationships. The regression model parameters reveal the maximum F (F-intercept), V (V-intercept), and power (P) producing capacities of the tested muscles. The aim of the present study was to evaluate the level of agreement between the routinely used "multiple-load model" an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 19 publications
5
54
1
Order By: Relevance
“…The high level of agreement between the 2 methods is comparable to the level of agreement observed from 4 different functional tests when the force-velocity relationship of the tested muscles was observed from a number of loading conditions using a linear regression model and from just 2 loads, i.e. the '2-load method' [30]. Of particular interest could be that the 2-velocity method could also reveal valid indices of maximum force (i.e.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The high level of agreement between the 2 methods is comparable to the level of agreement observed from 4 different functional tests when the force-velocity relationship of the tested muscles was observed from a number of loading conditions using a linear regression model and from just 2 loads, i.e. the '2-load method' [30]. Of particular interest could be that the 2-velocity method could also reveal valid indices of maximum force (i.e.…”
Section: Discussionsupporting
confidence: 60%
“…However, most of the available data sets suggest that the 'curvilinearity' could mainly originate from the inclusion of the relatively high isometric force, while the ranges of angular velocities typically applied provide an approximately linear relationship between the measured force and velocity [4,6,8,12,24,28]. Moreover, if the force-velocity relationship of individual muscle groups proves to be strong and approximately linear within a wide range of angular velocities, a similar approach to the recently proposed '2-load method' could be applied in routine testing [14,30]. Specifically, it has been shown that the functional movements tested under only 2 distinctive loads could provide almost identical outcomes as the same movements tested under variety of external loads that inevitably require regression modeling, as well as a prolonged and fatigue-prone testing procedure.…”
Section: A Novel Two-velocity Methods For Elaborate Isokinetic Testingmentioning
confidence: 99%
“…In any case, the 3-L protocol showed good reliability for F 0 , V 0 and L opt (CV < 10 %; ICC > 80), and excellent reliability for P max (CV = 4.3 %; ICC = 0.97), while maintaining the same ability to predict SPPB values as the extended protocol. Other authors have proposed and validated the application of a short protocol in young adults by which the F-V relationship can be deduced through the evaluation of only 2 loads [31,39]. Though it might be an advantageous approach for experienced young adults, we recommend avoiding the use of a 2-load protocol in older adults.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the evaluation of the F-V relationship can be a time-consuming and fatiguing task for an older subject, who has to perform a relatively high number of repetitions against different loads/velocities to draw the whole F-V relationship. Fortunately, the F-V relationship during multi-joint movements has been shown to follow a strong linear regression pattern [4,23], which permits the F-V relationship to be accurately drawn from a few F-V points by means of a linear regression equation [39], something that could facilitate the evaluation of the F-V relationship in older adults. However, whereas in young adults a recent study demonstrated that a two-load method was a feasible approach to assess the F-V relationship in an upper-body resistance exercise [31], the validity and reliability of the determination of the F-V relationship through the evaluation of a few loads have not been previously analyzed in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these results further support the high linearity of the F-V relationship that has been described for several exercises (e.g., vertical jumps, running, cycling, bench pull, BPT, leg extension, etc.) (Cross et al, 2018;García-Ramos et al, 2018b;García-Ramos et al, 2016;Iglesias-Soler et al, 2018;Lemaire et al, 2014;Zivkovic et al, 2017).…”
Section: Table 1] [Table 2] [Figure 2] Concurrent Validity Of the F-vmentioning
confidence: 99%